2021
DOI: 10.1186/s12888-021-03459-w
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis of depression and anxiety among medical students during COVID-19 epidemic

Abstract: Objective The novel coronavirus disease 2019 (COVID-19) is a global public health emergency that has caused worldwide concern. The mental health of medical students under the COVID-19 epidemic has attracted much attention. This study aims to identify subgroups of medical students based on depression and anxiety and explore the influencing factors during the COVID-19 epidemic in China. Methods A total of 29,663 medical students were recruited during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 62 publications
(50 reference statements)
4
23
1
Order By: Relevance
“…None had a severe depression disorder. This indicated that most medical students had strong psychological adjustment abilities and adaptability during the pandemic period, which is consistent with previous studies ( 18 , 36 ). Another reason for this might be the enhanced prevention and control behaviors of postgraduates.…”
Section: Discussionsupporting
confidence: 92%
“…None had a severe depression disorder. This indicated that most medical students had strong psychological adjustment abilities and adaptability during the pandemic period, which is consistent with previous studies ( 18 , 36 ). Another reason for this might be the enhanced prevention and control behaviors of postgraduates.…”
Section: Discussionsupporting
confidence: 92%
“…Guo L et al identified three latent classes of health behaviour reported by people at high risk of stroke, and this study had significance for the promotion of adaptive health behaviour in individuals at high risk of stroke [ 23 ]. Liu et al categorized medical students based on their depression and anxiety symptoms and suggested that school administrative departments carry out targeted psychological counselling based on different subgroups to promote the physical and mental health of medical students [ 10 ]. Warren CM et al employed LPA to identify whether psychosocial factors clustered together in different patterns among early adolescents and suggested that adolescents engaging in obesogenic and substance use behaviours may share common profiles of psychosocial risk [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, mental health promotion and prevention interventions would be tailored to the differing needs of distinct student subgroups rather than treating all students as a homogeneous group [ 7 , 9 ]. There is a substantial body of evidence regarding subgroup identification in mental health [ 10 12 ]. However, these studies seldom focus on adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the findings of this study indicated that RD with a history of psychological or emotional counseling before infection might be at higher risk of anxiety. Evidence suggested that individuals with a history of psychological counseling might have experienced psychological distress before, and the distress was more likely to reoccur due to COVID-19 infection among RD [ 78 , 79 ]. This finding suggested that more attention should be paid to the mental health of RD with a history of psychological or emotional counseling, and it is essential to prevent the reoccurrence of psychological problems among this population.…”
Section: Discussionmentioning
confidence: 99%